DAMPAK PENERAPAN KONSEP DESAIN MAGNETIC GEAR PADA PUTARAN GENERATOR - Normansyah Normansyah (Electrical Network Systems and Sources, 2022)
Alternating current electric generators are widely known in the world of electricity. All electric generators that until now were known to experts in this field require an increase in activation power because an electrical load is required from the electric generator. In other words, with the increase in the electrical load on the generator, the more power will be needed by the driver, whether it is fossil fuel generation, hydropower, or something else. The generator is an important component in the power plant. Generator is a design of an electric machine that can convert kinetic energy into electrical energy. The magnetic field will rotate in accordance with the direction of rotation when the generator gets a rotation from the outside which then results in electromagnetic induction in the coil. In this process, obtain data by plunging directly into the location of the process of rolling generators or electric motors of mechanical and welding workshops. As well as getting other information about the problems contained in the field such as: determining the coil and the coil rolling process, being able to measure and knowing the strength of the coil current, being able to find out the turning process and drilling the main material of the generator. So the impact of applying magnetic gear at a revolution of 375 rpm, the condition of the rotation of the generator without load. And the impact of applying magnetic gear at a revolution of 366 rpm, the condition of the generator rotation after loading. To reduce the increase in power required by the cruster due to the increase in the electrical load on the generator so that it can result in efficiency and reduce the cost of producing electrical energy in the generator.